Analysis Of The Relationship Between Industrial Practice Experience To The Intrepreneurship Of Students Of Pkk Study Program FPP UNP - Mudhiah, Putri Khansa; Siregar, Juliana; Fridayati, Lucy; Indrayeni, Wiwik (Universitas Negeri Padang, 2025)
Indonesia is currently still not said to be a developed country, because there is still a small number of people who have an interest in entrepreneurship. One of the factors that can affect the interest of entrepreneurs is education. At the Faculty of Tourism and Hospitality of Padang State University, there are courses that can support students' entrepreneurial interests, namely Industrial Field Experience (PLI). The purpose of this research is to find out the relationship between industrial field experience and entrepreneurial interest of PKK FPP UNP Study Program students.The research method used is quantitative with a correlational approach. The research population consists of 139 sampling techniques with a random sampling probability of 58. Data collection techniques include questionnaires, while data analysis uses normality tests, linearity tests, and hypothesis tests.The results of the t-test hypothesis of industrial field experience are positively related to entrepreneurial interest with a correlation value of 0.001 and a significance of and obtained by t_hitung>t_table (3.449 > 1.672) with α = 0.05. From the hypothesis, Ha's hypothesis which reads that there is a relationship between industrial field experience and entrepreneurial interest is accepted and Ho is rejected.